From Creation to Evaluation: A Comprehensive Global Health Scholars Program for Graduate Medical Education Trainees. (August 2020) - Morgan, Jennifer; Galvin, Shannon; Goldstein, Joshua; Fant, Colleen; Murphy, Robert; Doobay-Persaud, Ashti
Introduction: Recently, participation in clinical global health rotations has significantly increased among graduate medical education (GME) trainees. Despite the many benefits these experiences provide, many ethical challenges exist. Well-intentioned partnerships and participants often encounter personal and professional dilemmas related to safety, social responsibility, and accountability. We designed a curriculum to provide trainees of all specialties with a comprehensive educational program aimed at delivering culturally mindful and ethically responsible clinical care in resource-constrained settings. Methods: The McGaw Global Health Clinical Scholars Program (GHCS) at Northwestern University offers a 2-year curriculum for selected GME trainees across specialties interested in global health. Each trainee must complete the following components: core lectures, peer journal club, specialty-specific lectures, a mentorship agreement, ethics and skill-based simulations, a global health field experience, a poster presentation, and a mentored scholarly project. Results: Since 2014, 84 trainees from 13 specialties have participated in the program with 50 current trainees and 39 graduates. Twenty-five trainees completed exit surveys, of which 95% would recommend this program to other trainees and 84% felt more prepared to deliver global health care. In addition, 78% reported career plans that included global health and/or work with underserved populations. Trainees described "acceptance of differences and respect for those differences" and "understanding sustainability" as learning points from the program. Discussion: Providing a comprehensive global health education program across specialties can be feasible and effective. GME trainees who participated in this program report feeling both more prepared for clinical experiences and more likely to serve the underserved anywhere.